Modeling of Paper-Wrinkle Generation Process - HARADA, Yoshihiro; MATSUMOTO, Shogo (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series C, 2012)
One of the main issues in the development of printers is to achieve sheet-feeding stability with various kinds of sheets and to shorten the development period. In recent years, studies on sheet handling mechanisms have been performed that enable us to develop a sheet-feeding path efficiently; however, defects resulting from sheet-feeding instability still occur because many defects cannot be treated analytically. To achieve efficient development condition of printers, mechanism analysis of the paper-wrinkle generation phenomena in fuser unit has been conducted. A convenient geometry model of the paper-wrinkle has been constructed based on the observation of the generation process, and the wave slope angle as an alternative characteristic of the wrinkle generation has been derived. In addition, principle analysis equipment has been developed to measure the paper feeding velocity distribution and the transformation of the deformed paper. As a result, relationship between the roller shape and the generation process of the paper-wrinkle has been evaluated quantitatively, and the validity of the wave slope angle as the alternative characteristic has been verified.